Children's screen use and school readiness at 4-6 years: prospective cohort study - Leigh M. Vanderloo; Magdalena Janus; Jessica A. Omand; Charles D.G. Keown-Stoneman; Cornelia M. Borkhoff; Eric Duku; Muhammad Mamdani; Gerald Lebovic; Patricia C. Parkin; Janis Randall Simpson; Mark S. Tremblay; Jonathon L. Maguire; et al. (BMC, 2022)
Abstract Background The primary aim of this study was to determine if screen use in early childhood is associated with overall vulnerability in school readiness at ages 4 to 6 years, as measured by the Early Development Instrument (EDI). Secondary aims were to: (1) determine if screen use was associated with individual EDI domains scores, and (2) examine the association between screen use and EDI domains scores among a subgroup of high screen users. Methods This prospective cohort study was carried out using data from young children participating in a large primary care practice-based research network in Canada. Logistic regression analyses were run to investigate the association between screen use and overall vulnerability in school readiness. Separate linear regression models examined the relationships between children's daily screen use and each separate continuous EDI domain. Results A total of 876 Canadian participants participated in this study. Adjusted logistic regression revealed an association between increased screen use and increased vulnerability in school readiness (p = 0.05). Results from adjusted linear regression demonstrated an association between higher screen use and reduced language and cognitive development domain scores (p = 0.004). Among high screen users, adjusted linear regression models revealed associations between increased screen use and reduced language and cognitive development (p = 0.004) and communication skills and general knowledge domain scores (p = 0.042). Conclusions Screen use in early childhood is associated with increased vulnerability in developmental readiness for school, with increased risk for poorer language and cognitive development in kindergarten, especially among high users.